(untitled) - Smith, Michael (Hoboken, N.J., 2020)
The Sixth Edition brings the text completely current with the most recent organic reactions. In addition, the references have been updated to enable readers to find the latest primary and review literature with ease.
Keywords: Chemistry, Organic,Hóa hữu cơ